Influência do metacaulim na durabilidade de concretos usuais de mercado sujeitos à carbonatação acelerada - Perim, José Roberto (2013)
The concrete, to be one of the most consumed material in the world, has been the object of several studies and researches in order to improve and enhance its features with respect to technical, economical and environmental aspects, aiming a higher durability. Solutions have been searched and actions have been implemented in order to produce such concrete and to achieve these goals. One of which is the incorporation of mineral additions to replace part of the Portland cement used in the production of this material. Several additions have been studied over time, among them are the fly ash, the slag blast furnace, the silica fume, the ash from rice husk, the bagasse ash from sugar cane and the metakaolin. The latter is a high reactivity pozzolan and it is being studied to be an alternative material of great potential and abundance, it is found in several parts of the world and it has a great number of advantages, such as ease of exploration, the use of a relatively simple process in its industrialization, the low cost of production and trade, besides a lower environmental impact when compared to the clinker. Several researches have already proved its potential as pozzolanic material, however, a few studies have been conducted in order to verify the durability of concretecurrent market with the addition of metakaolin. The carbonation, which is, simplifying, a chemical reaction between the carbon dioxide from the air and the calcium hydroxide present in cement paste, and occurs in the surface layers in contact with the environment to which the concrete is exposed, is one of the most important phenomenon to the beginning of the process of corrosion that causes major problems related to the lack of durability of structures, can lead to the collapse of structures. In this research, two groups of concrete were studied. In the first group were addressed levels of 10%, 12,5%, 15%, 17,5% and 20% of metakaolin in replacement of the cement and with the same relation a/ag (0,60). And in the second group were used the substitution levels of 10%, 15% and 20%, keeping the same range of resistance with variation of the ratio a/ag. The behavior of these concrete was analyzed in relation of its resistance to compressive strength at ages 3, 7, 28, 56 and 91 days, to water absorption by immersion at 91 days, and to microstructural and mineralogical changes. It as also evaluated the advancing front of carbonationmeasurements of the depth of the carbonation and mass gain during 16 weeks after preconditioning, where these concrete were subjected to accelerated carbonation process in a CO2 incubator, whose parameters used were as follows: temperature of 20°C, 75% relative humidity and CO2 concentration from 6%. The results showed that as the level of metakaolin increases, there are strength gains by compression, reaching levels between 8% and 16% higher than the reference concrete. Regarding the carbonation process, the behavior of the concrete of the first group was very similar to the reference concrete, and that levels 10% and 15% of substitution had the best performances. The concrete of the second group performed well below the other group, showing the great influence of ratio a/g related to carbonation.